Hormesis Research in China Is More Prevalent than Previously Thought - Evgenios Agathokleous PhD; Caiyu Geng BSc; Boya Zhou MSc; Haoyu Sun PhD; Jiahua Guo PhD; Jing Zhang PhD; Fuxing Zhu PhD (SAGE Publishing, 2022)
An analysis of China's domestic publications revealed that China's hormesis-related research was enormously underestimated. China's documented hormesis-related research spans at least four decades, covers a broad spectrum of research areas, and is more abundant than previously thought. These findings should be considered in historical assessments of the concept of hormesis. Moreover, similar to the international literature, different terms have been used to describe the same phenomenon (hormesis), which hampers communication, generalization of findings and accumulation of knowledge. Hence, we advocate that 'hormesis' should be cited as a keyword in all the relevant publications written in Chinese language.